Determinação do conteúdo fenólico, flavonoides e atividade antioxidante nas folhas de dez cultivares de Ipomoea batatas (l.) lam. desenvolvidas para produção industrial de etanol - Soares, Ilsamar Mendes (Universidade Federal do Tocantins, 2017)
This study aimed to determine the main phenolic constituents and evaluate the antioxidant potential of the leaves of ten cultivars of Ipomoea batatas, all directed from improvement genétic for the industrial production of ethanol. To that end, leaves were collected from mature plants, which were dried, reduced to powder and subjected to extraction by refluxing in Soxhlet with ethanol 70 %, followed by lyophilization. There were prospects of phytochemical extracts by different chemical reactions and CCD, which revealed the presence of phenolic general, anthraquinones, alkaloids, saponins, flavones, flavanols, xanthones, catechins, general tannins, gallic tannins and flavonoids. The total phenolic content determined by the Folin-Ciocalteu and total flavonoids by reaction with aluminum chloride correlated with each other and varied among cultivars, being lower in Duda and cultivate greater in cultivar Lívia with phenols between 54.7170 ± 4.354 and 112.288 ± 3.653 mg ATE/g, flavonoids ranging from 29.155 ± 3.725 to 97.358 ± 2.128 mg RE/g. The levels of these compounds correlated with the antioxidant activities determined by DPPH and FRAP methods also varied among cultivars and showed up in all good except the cultivar Duda that such activity was moderate. Moreover, there was a low correlation between phenol content and total flavonoids with activity determined by reaction with chelating ferrozina and ferrous sulfate. This varied among cultivars and cultivar was more efficient in Duda. Analysis by HPLC-UV VIS at 280 nm revealed a complex array of phenolic compounds in the extract of the cultivars under study and identify possible 10 substances, ellagic acid, gallic acid, (-)-gallocatechin, (+)-catechin, rutin, quercetin, naringin, (+ / -)-naringenin, myricetin, luteolin and morin. Results showed great potential use of phenolic compounds from the leaves of I. batatas as an option for diversification of products derived from the culture of sweet potato, a fact that makes these parts of the plant attractive to continuous research and perhaps future application in medicine.